Treatment patterns, adherence to international guidelines, and financial mechanisms of the market access of advanced breast cancer therapy in Bulgaria - Karanyotova, Stephanie; Topova, Branimira; Petrova, Elina; Doychev, Peter; Kapitanska, Eliana; Petrova, Guenka; Mitkova, Zornitsa; Dimitrova, Maria (Frontiers in Public Health, 2023)
Breast cancer is the most common cancer among women in Europe. Advanced breast cancer (ABC) poses a significant therapeutic challenge and therefore timely access to treatment is crucial. The aim of the study was to evaluate the treatment patterns and patients' access to new therapies for ABC in Bulgaria. We conducted retrospective study for the period 2008-2021. Based on EMA database we analysed the number of medicinal products with marketing authorization for ABC in the last 13 years. Time to market access was evaluated as the degree of availability, measured by the number of medicines available to patients (Availability Index, AI) and the average time between obtaining a marketing authorization and time to inclusion in the Positive Drug List. Data were analysed with descriptive statistics in Microsoft Excel. The average time to access was 564 days for targeted therapy. The availability and compliance index for chemotherapy and hormonal therapy in advanced breast cancer was 1, while the average AI for targeted therapy is 0.67. Patient access to targeted oncology therapy of ABC is above the average for Europe and takes 1-2 years. Faster access is more evident for biosimilars. National regulatory requirements for pricing and reimbursement have major impact on market access.